Challenges faced by gay and lesbian students at the University of Limpopo (Turfloop Campus) - Letsoalo, Daniel Lesiba (University of Limpopo, 2016)
A qualitative study was conducted to investigate challenges faced by gay and lesbian students at the University of Limpopo (Turfloop Campus). Semi-structured interviews were used for data collection. Purposive sampling (snowball sampling) was used to find participants for focus groups. Data were analysed using Thematic Content Analysis (TCA). The results of this study gave an insight into challenges faced by lesbian and gay students at the University of Limpopo (Turfloop Campus). It also indicated the impact of these challenges on their psychological, emotional and academic functioning. Results indicate that gay and lesbian students face a multitude of problems on campus environment which includes among other things bullying, discrimination, victimisation, abuse, academic disruption and derogatory remarks from their peers (heterosexual students) and staff members. KEYWORDS: Homophobia, LGBTI, Discrimination, Prejudice, sexuality.
Thesis (M. A. (Clinical Psychology)) -- University of Limpopo, 2016
Keywords: Homophobia; LGBTI; Discrimination; Prejudice; Sexuality; Homosexuality.